Pokhmursky V.V., Vynar V.A., Vasyliv Kh. B., Zakiev V.I., Ratska N.B. Peculiarities microstrain of surface layers and mechanisms wear α-titanium under the influence of hydrogen. - Похмурський, В.І; Винар, В.А; Василів, Х.Б.; Закієв, В.І.; Рацька, Н.Б. (Problems of Tribology, 2014)
The peculiarities of surface layers microdamage and mechanisms of wear of titanium BT1-0 after electrolytic hydrogenation has been investigated. The concentration of hydrogen in the surface layers of titanium after hydrogenation at current density 1 A/dm2 during 1 h corresponding equilibrium, and at 2 A/dm2 exceeds the 1.5 times due to the formation of hydride phases (TiH2 ). Internal stress in the crystal lattice of titanium after hydrogenation increased by 19 %, leading to an increase in microhardness by 20 % and modulus by 15 %. At the same time significantly (by 40 %) reduced the volume of material recovery work after the elastic deformation and de 6 % - after the plastic deformation. Reduction of elastic-plastic deformation work leads to reducing friction coefficient of titaqnium in 2 ... 3 times compared with the initial state. Wear occurs due to cracking and brittle fracture of surface layers. The plastic deformation of microasperities dominates after abrasion of hydrogenated layer.